2022
DOI: 10.1093/iob/obac041
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Hatching of Red-Eyed Treefrog Embryos: Hydration and Clutch Structure Increase Behavioral Thermal Tolerance

Abstract: Climate change is increasing both environmental temperatures and droughts. Many ectotherms respond behaviorally to heat, thereby avoiding damage from extreme temperatures. Within species, thermal tolerance varies with factors such as hydration as well as ontogenetic stage. Many tropical anurans lay terrestrial eggs, relying on environmental moisture for embryonic development. These eggs are vulnerable to dehydration, and embryos of some species can hatch prematurely to escape from drying eggs. Warmer temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Although the impact of temperature extremes on ectotherm embryos has been extensively studied, our knowledge is largely biased toward thermal tolerance of embryos from thermally challenging habitats (Angilletta et al, 2013; Guevara‐Molina et al, 2022; Hall & Warner, 2019). In this study, we focused on amphibian embryos from relatively cold aquatic habitats and revealed that thermal extreme events have various nonlethal effects on embryonic life histories and larval behavior (see also Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of temperature extremes on ectotherm embryos has been extensively studied, our knowledge is largely biased toward thermal tolerance of embryos from thermally challenging habitats (Angilletta et al, 2013; Guevara‐Molina et al, 2022; Hall & Warner, 2019). In this study, we focused on amphibian embryos from relatively cold aquatic habitats and revealed that thermal extreme events have various nonlethal effects on embryonic life histories and larval behavior (see also Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The eggs are deposited on plants above water (Duellman, 1970) and, without disturbance, hatching occurs after 6–7 days in our Gamboa, Panama, study population (Warkentin, 2005). However, A. callidryas embryos can hatch early and escape in response to multiple natural risks, including attacks by egg‐eating snakes and wasps (Warkentin, 1995, 2000), infection by a fungal pathogen (Warkentin et al, 2001), flooding (Warkentin, 2002), dehydration (Salica et al, 2017), and dangerously high temperatures (Guevara‐Molina et al, 2022). Previous research has documented that physical disturbance cues, sensed by the inner ear and lateral line mechanoreceptors, mediate predator‐induced hatching (Jung et al, 2019, 2020; Warkentin, 2005) and that hypoxia cues flooding‐induced hatching (Warkentin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…2-6.8, N = 7 clutches;Cohen et al, 2019). In contrast, drying eggs reached only 4.0 ± 0.34 mm(3.3-4.8, N = 15 clutches) at 2 days, then shrank to 3.7 ± 0.36 mm (2.9-4.4 mm) by 4 days, when induced hatching began(Salica et al, 2017) Guevara-Molina et al (2022). report even greater variation in egg size with (de)hydration, ranging from 2.8 to 7.5 mm diameter, or 11-218 µL volume.…”
mentioning
confidence: 96%
See 2 more Smart Citations